Optimalisasi fungsi perpustakaan sekolah sebagai pusat informasi kesehatan bagi siswa: Pengalaman pengabdian masyarakat di SD Kristen Kota Kendari - La Ode Liaumin Azim; Akifah Akifah; Agnes Mersatika Hartoyo (Nur Science Institute, 2025)
The library's function as a health information center has not been fully utilized in many schools. This results in students' lack of understanding of the importance of easily accessible health information through the library. This community service program aims to optimize the library at SD Kristen Kota Kendari as a health information center for students. In this effort, the library was revitalized through improvements to the room layout, grouping book collections by theme, and the development of a health literacy corner. In addition, health education was provided to students through group reading activities and discussions on topics such as personal hygiene, the importance of handwashing, and healthy eating. Students' knowledge was assessed before and after the health education using a structured questionnaire. The results showed a significant increase in students' understanding. Most students who initially had poor knowledge moved to a better knowledge category after the education. The revitalization of the library and health literacy activities proved effective in increasing students' interest in reading and their understanding of the importance of clean, healthy living behaviors.